Analisis Sifat Kimia Tanah yang ditanami Tanaman Kacang Hijau (Vigna radiata L.) Di Desa Naiola Kecamatan Bikomi Selatan - Tuas, Maria Angelina; Neonbeni, Eduardus Yosef; Tobing, Wilda Lumban (Fakultas Pertanian, Sains, dan Kesehatan, Universitas Timor, 2024)
Soil is a part of the Earth's crust where living organisms thrive, composed of minerals and organic materials originating from weathering and sedimentation. The soil in Naiola Village is classified as entisol with a very thin soil solum (lithic), characterized by low organic content and a very low cation exchange capacity. Previous research, liquid organic fertilizer (POC) derived from tofu waste was applied to investigate the effects of concentration and application time on the growth and yield of mung beans. The main objective of this research is to determine several soil chemical properties of entisols after applying POC to mung bean plants in Niola Village, Bikomi Selatan Subdistrict, Timor Tengah Utara Regency. The research was conducted using a descriptive method with observational techniques. Soil samples were collected from two plots, namely the control plot (P0) and highest yield plot (P1), at the mung bean plantation and subsequently analyzed in the laboratory to obtain quantitative data. The analyzed parameters are; water content and soil pH. The highest water content was 0.23% and the highest pH was 7.70.